Methods of suicide used by people with cancer: a scoping review protocol [version 2; peer review: 2 approved] - Daisy Wiggin; Eugene Cassidy; Doireann Ni Dhalaigh; Paul Corcoran; Fahmi Ismail; Zubair Kabir (HRB Open Research)
Background People with cancer are at a higher risk of suicide than the general population. Access to means of suicide is an important volitional risk factor, that if targeted at a population level can reduce incidence of suicide deaths. People with cancer are often prescribed multiple medications that have a high case fatality when taken in overdose and therefore have increased access to specific means of high lethality self-harm. The aim of this review is to examine the methods of suicide used by people with cancer, the study designs used to explore these and what, if any, comparisons have been made to the general population. Methods This scoping review will follow JBI scoping review methodology guidelines and be reported according to PRISMA-ScR checklist; a systematic search will be conducted of Embase (Elsevier), CINAHL Plus (EBSCO), PsycINFO (EBSCO), PsychARTICLES(EBSCO), and PubMed (NCBI) databases and grey literature sources. A data collection tool will be specifically designed and piloted independently by two reviewers. Findings will be presented descriptively, graphically, and narratively. Results The results of this review will identify the breadth of evidence in relation to methods of suicide used by people with cancer, explore how different methods are defined and categorised, how the topic has been studied, and ascertain if a systematic review is possible.